Relationship between Operative Time and Complications for Impacted Mandibular Third Molar Removal - Baloch, Paras Rahim; Punjabi, Suneel Kumar; Hamid, Shuja; ., Priya (Journal of Liaquat University of Medical & Health Sciences, 2019)
OBJECTIVE: To identify relationship between operative time and surgical complications encountered during and soon after removal of impacted 3rd Molar teeth. METHODOLOGY: This cross-sectional study was conducted at the department of Oral & Maxillofacial Surgery, Faculty of Dentistry, Liaquat University of Medical & Health Sciences, Jamshoro from February 2017 to July 2017. Total ninety two surgical removals were done after pre-operative assessment of impaction. Operative time was recorded. Any intra-operative complication was noted during surgery and postoperative complications were recorded on 3rd, 5th and 7th day. The Data was analysed by statistical software package SPSS version 20.0 Qualitative variables were expressed as absolute frequencies and percentages. The variables were presented as mean, frequencies/percentages. RESULTS: The results of this study showed that surgical removal of third molar was more common in females (58%) with the highest percent of mesioangular (39%).The pre-operative pain was more in females and older patients. In intraoperative complication, injury to soft tissue was more common than other complications. In postoperative complications, swelling and trismus were more on the 3rd day. CONCLUSION: The inflammatory complications that can be considered (pain, swelling and trismus) after third molar surgery remain an important factor at the early postoperative periods. The intraoperative and postoperative complication also depends on surgeons experience and duration of procedure which may increase or decrease the sequela of removal impacted teeth.